Best Answer

If you're looking to solve for x, you can do so as follows:

x2 + 12x - 6 = 0

x2 + 12x + 36 = 42

(x + 6)2 = 42

x + 6 = ± √42

x = -6 ± √42

Q: X2 plus 12x-6 equals 0

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

x2 + 7x = 2x2 + 6 x2 - 2x2 + 7x = 6 -x2 +7x - 6 = 0 or alternatively x2 - 7x + 6 = 0

x2 + 49 = 0 ∴ x2 = -49 ∴ x = 7i

-2

No.

168

Related questions

x2 plus 3x plus 3 is equals to 0 can be solved by getting the roots.

x2 + 7x = 2x2 + 6 x2 - 2x2 + 7x = 6 -x2 +7x - 6 = 0 or alternatively x2 - 7x + 6 = 0

no

x2 + 49 = 0 ∴ x2 = -49 ∴ x = 7i

-2

No.

168

x2 + 10x = 0 x2 + 10x + 25 = 25 (x + 5)2 = 25 x + 5 = +-5 x1 = 0 x2 =10

If: y = x2+20x+100 and x2-20x+100 Then: x2+20x+100 = x2-20x+100 So: 40x = 0 => x = 0 When x = 0 then y = 100 Therefore point of intersection: (0, 100)

x2-5-4x2+3x = 0 -3x2+3x-5 = 0 or as 3x2-3x+5 = 0

x = -3.27 or -6.73

Yes